If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + -3x) + 12 = 7x + -5(2x + -7) (4 * 2 + -3x * 2) + 12 = 7x + -5(2x + -7) (8 + -6x) + 12 = 7x + -5(2x + -7) Reorder the terms: 8 + 12 + -6x = 7x + -5(2x + -7) Combine like terms: 8 + 12 = 20 20 + -6x = 7x + -5(2x + -7) Reorder the terms: 20 + -6x = 7x + -5(-7 + 2x) 20 + -6x = 7x + (-7 * -5 + 2x * -5) 20 + -6x = 7x + (35 + -10x) Reorder the terms: 20 + -6x = 35 + 7x + -10x Combine like terms: 7x + -10x = -3x 20 + -6x = 35 + -3x Solving 20 + -6x = 35 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 20 + -6x + 3x = 35 + -3x + 3x Combine like terms: -6x + 3x = -3x 20 + -3x = 35 + -3x + 3x Combine like terms: -3x + 3x = 0 20 + -3x = 35 + 0 20 + -3x = 35 Add '-20' to each side of the equation. 20 + -20 + -3x = 35 + -20 Combine like terms: 20 + -20 = 0 0 + -3x = 35 + -20 -3x = 35 + -20 Combine like terms: 35 + -20 = 15 -3x = 15 Divide each side by '-3'. x = -5 Simplifying x = -5
| -3(8k-3)=-17+2k | | 7(x-1)+3= | | 2(x-2)/3+5x=10 | | 3w-5+3w-5= | | 2(x-2)/5+5x=10 | | 240/275 | | 4x-(x^2)=0 | | 55x=1 | | 11x^2-28x-15=0 | | 25a^2+60ab+36b^2-64=0 | | 3x/5-0.5+1.9 | | (15/1)/(-3/4) | | x=180-(90-x)-4 | | 6(x+2)+10x=8x+3(x-9) | | x=180-((90-x)-4) | | 15/1/-3/4 | | x/6-x+3/5=1 | | 6x+9=9x+3 | | r+5/3=-6 | | M-12=18 | | .75y-5=-.5y+4 | | .75y-5=-.5y+5 | | -0.5=d/9 | | 9t-6-6t=7 | | y/8+4=-15 | | 3(x-6)+8=5x-2 | | 2y^2-2y=84 | | 10z-3z-2=24-2z | | 10(3x-10)=4(5x-10) | | 3x/6-(x-2)/2=(x-1)/4 | | 10(3x-10)=4(5x+10) | | 4(3x-8)+9=12x-23 |